LiNi0.5Mn1.5O4 Cathode Materials Co-Doped with La3+ and S2− for Use in Lithium-Ion Batteries - Wencong WANG; Hiromasa HANZAWA; Ken-ichi MACHIDA; Kohei MIYAZAKI; Takeshi ABE (Electrochemistry, 2022)
Spherical LiNi0.5Mn1.5O4 particles co-doped with lanthanum (La) and sulfur (S) were synthesized by a facile co-precipitation assisted solid-state annealing method with stable oxysulfide La2O2S (x = 0, 0.3, 0.5, 0.7, 1.0, and 1.2 at%) as a dopant. The prepared composite materials exhibited a slight shrinkage of lattice parameters without any impurity phase under x ≤ 0.7 at%, and the Ni/Mn disordered arrangement in the spinel lattice increased with an increase in the ratio of dopants, as confirmed by X-ray diffraction and Raman spectroscopy. X-ray photoelectron spectroscopy and electrochemical measurements also clearly indicated that the residual Mn3+ in the cubic lattice could be effectively eliminated with the use of La2O2S dopants. The composite materials showed outstanding rate and cycling performance compared with those of the pristine material. Specifically, the material doped with 0.5 at% La2O2S showed a high reversible capacity of 115.9 mAh g−1 at 10 C, and a remarkable cycling performance of 109.2 mAh g−1 even after 200 cycles. All of these extraordinary performances were attributed to the synergistic effects of La and S in the spinel structure, which induce a suitable pathway for lithium ion and a robust architecture during the electrochemical assessment.